Acronym-Expansion Disambiguation for Intelligent Processing of Enterprise Information - Hwang, Myunggwon; Jeong, Do-Heon; Kim, Jinhyung; Song, Sa-Kwang; Jung, Hanmin; Mazhar, Sajjad (Computing and Informatics, 2015)
An acronym is an abbreviation of several words in such a way that the abbreviation itself forms a pronounceable word. Acronyms occur frequently throughout various documents, especially those of a technical nature, for example, research papers and patents. While these acronyms can enhance document readability, in a variety of fields, they have a negative effect on business intelligence. To resolve this problem, we propose a method of acronym-expansion disambiguation to collect high-quality enterprise information. In experimental evaluations, we demonstrate its efficiency through the use of objective comparisons.